Keterkaitan Antara Kelimpahan Zooplankton dengan Fitoplankton dan Parameter Fisika-Kimia di Perairan Jailolo, Halmahera Barat - ., Yuliana (UNIVERSITAS SRIWIJAYA, 2014)
Zooplankton have an important role in water especially in the food chain, this organism is a consumer Ã‚Â I whichÃ‚Â plays a major role in bridging the energy transfer from primary producers (phytoplankton) to living things areÃ‚Â at Ã‚Â a Ã‚Â higher Ã‚Â trophic Ã‚Â level Ã‚Â (fish Ã‚Â and Ã‚Â shrimp). Ã‚Â This Ã‚Â research Ã‚Â aimed Ã‚Â to Ã‚Â analyze Ã‚Â the Ã‚Â relationship Ã‚Â between Ã‚Â theÃ‚Â abundance Ã‚Â of Ã‚Â zooplankton Ã‚Â to Ã‚Â phytoplankton Ã‚Â and Ã‚Â phisic-chemistry Ã‚Â parameters Ã‚Â at Ã‚Â Jailolo Ã‚Â waters, Ã‚Â HalmaheraBarat. Ã‚Â The Ã‚Â research Ã‚Â was Ã‚Â conducted Ã‚Â in Ã‚Â February Ã‚Â 2011. Ã‚Â The Ã‚Â observation Ã‚Â of Ã‚Â zooplankton Ã‚Â were Ã‚Â taken Ã‚Â from Ã‚Â 7Ã‚Â stations by filtration method. The result showed that there were 7 genera of 4 (four) groups: Ciliate(1 genus),Ã‚Â Crustaceae Ã‚Â (4 Ã‚Â genera), Ã‚Â Rotifera Ã‚Â (1 Ã‚Â genus), Ã‚Â and Ã‚Â Sarcodina Ã‚Â (1 Ã‚Â genus). Ã‚Â Abundance Ã‚Â of Ã‚Â zooplankton Ã‚Â range Ã‚Â fromÃ‚Â 1,429 - 32,571 cell/m3, the highest on Gufasa and Tuada (32,571 cell/m3) and the lowest on Bobanehena (1,429Ã‚Â cell/m3). Ã‚Â Ã‚Â The Ã‚Â value Ã‚Â range Ã‚Â of Ã‚Â zooplankton Ã‚Â biological Ã‚Â index Ã‚Â were Ã‚Â diversity Ã‚Â index Ã‚Â (H Ã‚Â ') Ã‚Â = Ã‚Â 0.4506 Ã‚Â to Ã‚Â 1.5091,Ã‚Â equitability index (E) = 0.6356 to 0.9710, and the Ã‚Â dominance index (D) = 0 , 2379 to .7222. There is Ã‚Â a closeÃ‚Â relationship Ã‚Â between Ã‚Â the Ã‚Â abundance Ã‚Â of Ã‚Â zooplankton Ã‚Â to Ã‚Â phytoplankton Ã‚Â abundance Ã‚Â and Ã‚Â physico-chemicalÃ‚Â parameters Ã‚Â of Ã‚Â waters, Ã‚Â with Ã‚Â a Ã‚Â coefficient Ã‚Â of Ã‚Â determination Ã‚Â (R2) Ã‚Â of Ã‚Â 0.972 Ã‚Â and Ã‚Â the Ã‚Â regression Ã‚Â equation Ã‚Â Y Ã‚Â = Ã‚Â -Ã‚Â 7194397 - 0.0836 phytoplankton + 269630 temperature+ 6195 salinity + 140943 DO - 128086 pH.